Phosphocyclocreatine is the dominant form of cyclocreatine in control and creatine transporter deficiency patient fibroblasts - Kirill Gorshkov; Amy Q. Wang; Wei Sun; Ethan Fisher; Marta Frigeni; Marc Singleton; Natasha Thorne; Bradley Class; Wenwei Huang; Nicola Longo; Minh‐Ha T. Do; Elizabeth A. Ottinger; et al. (Wiley, 2019)
Abstract Creatine transporter deficiency (CTD) is a metabolic disorder resulting in cognitive, motor, and behavioral deficits. Cyclocreatine (cCr), a creatine analog, has been explored as a therapeutic strategy for the treatment of CTD. We developed a rapid, selective, and accurate HILIC ultra‐performance liquid chromatography‐tandem mass spectrometry (UPLC‐MS/MS) method to simultaneously quantify the intracellular concentrations of cCr, creatine (Cr), creatine‐d3 (Cr‐d3), phosphocyclocreatine (pcCr), and phosphocreatine (pCr). Using HILIC‐UPLC‐MS/MS, we measured cCr and Cr‐d3 uptake and their conversion to the phosphorylated forms in primary human control and CTD fibroblasts. Altogether, the data demonstrate that cCr enters cells and its dominant intracellular form is pcCr in both control and CTD patient cells. Therefore, cCr may replace creatine as a therapeutic strategy for the treatment of CTD.